1970
DOI: 10.3126/nepjoph.v4i1.5847
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and laboratory diagnosis of fungal corneal ulcer in the Sundarban Region of West Bengal, eastern India

Abstract: Introduction: Corneal ulcers are the second most-common cause of preventable blindness after cataract in tropical developing countries. Fungal corneal ulcers constitute 30 to 62 % of the total microbial culture-positive corneal ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 0 publications
2
17
1
Order By: Relevance
“…[1,2] These infections are caused by fungal penetration of a compromized corneal epithelium, typically following corneal trauma with vegetable matter. [3] While the prevalence of fungal keratitis is relatively high in tropical regions such as South India, Ghana, and China, [4][5][6][7][8][9] it is generally much lower in temperate regions such as the UK and the Northern United States. [4,10,11] However, there have been numerous case reports of fungal keratitis associated with both therapeutic and daily soft contact lens wear.…”
mentioning
confidence: 99%
“…[1,2] These infections are caused by fungal penetration of a compromized corneal epithelium, typically following corneal trauma with vegetable matter. [3] While the prevalence of fungal keratitis is relatively high in tropical regions such as South India, Ghana, and China, [4][5][6][7][8][9] it is generally much lower in temperate regions such as the UK and the Northern United States. [4,10,11] However, there have been numerous case reports of fungal keratitis associated with both therapeutic and daily soft contact lens wear.…”
mentioning
confidence: 99%
“…20 Various studies revealed the utility of KOH preparation in fungal corneal ulcers. 8,18,20,21,22 The sensitivity of KOH preparation has been found to be variable ranging between 33-94% as reported by various studies. The sensitivity and specificity of KOH preparation in our study was 45.45% and 75% respectively.…”
Section: Discussionmentioning
confidence: 94%
“…This was much different from other reported series. 20,21 In a study by Bandyopadhyay S et al, the sensitivity was 98.3% and specificity was 98.5%. Fungal Hyphae were seen by wet mount preparation in 80.9% cases and culture growth present in 88% cases as reported by V Sharma et al 20 The fungal culture positivity was 41% in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations